Potential role of irisin in lung diseases and advances in research - Hongna Dong; Xuejiao Lv; Peng Gao; Yuqiu Hao (Frontiers Media S.A., 2023)
Irisin, a myokine, is secreted by the movement of skeletal muscles. It plays an important role in metabolic homeostasis, insulin resistance, anti-inflammation, oxidative stress, and bone metabolism. Several studies have reported that irisin-related signaling pathways play a critical role in the treatment of various diseases, including obesity, cardiovascular disease, diabetes, and neurodegenerative disorders. Recently, the potential role of irisin in lung diseases, including chronic obstructive pulmonary disease, acute lung injury, lung cancer, and their associated complications, has received increasing attention. This article aims to explore the role of irisin in lung diseases, primarily focusing on the underlying molecular mechanisms, which may serve as a marker for the diagnosis as well as a potential target for the treatment of lung diseases, thus providing new strategies for their treatment.